Is there a duty upon the state to provide basic education to the undocumented immigrant child in South Africa - Mulumba, Tshilenge Jean-Paul (My University, 2014)
Children in South Africa have the right to basic education. The 1996 South African Constitution and the 1996 South African Schools Act guarantees this right. Together with the Convention on the Rights of the Child, which South Africa has signed and ratified, both domestic and international statutes require the state to support the educational system, managed and characterised by non-discrimination which considers the right of whoever lives under South African jurisdiction to have access to education. The focal point of this study is to examine the laws and practices concerning access to basic education for undocumented immigrant children in South Africa. It provides an examination of both domestic and international statutes related to the right of the immigrant child to access basic education. The main purpose of the study will be to establish, whether it is the state’s duty to provide basic education to undocumented immigrant children. The study offers recommendations for legislative reforms which contribute to the development of the education system in South Africa and elsewhere. In other words, this study will provide an in-depth examination of the legislation and practices relating to immigrants’ access to basic education in South Africa, and an analysis of whether the current policies and implementation are in line with domestic and international standards.